(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Labial adhesion (LA) is the most frequently encountered medical condition in paediatric surgery clinics among prepubertal girls. The highest incidence of LA occurs in toddler age groups, specifically between 1 and 3 years of age. This condition is usually asymptomatic and often arises without any other pathology affecting the upper genital tract. Objective: The aim of this study is to fill the gap in epidemiological data by investigating the prevalence, age at presentation, and patterns of labial adhesion among paediatric age groups in Bangladesh. Methods: A total of 345 cases of LA were seen during the study period on paediatric patients from 2017 to 2024 in a private care setting in Chattogram, Bangladesh. A comprehensive semi-structured questionnaire was used to collect sociodemographic information related to age, age groups, place of living, family history of LA, primary identifier, and referral system. Types of labial adhesion, clinical presentations, and associated anomalies were included as clinical questions in the questionnaire, ensuring a thorough data collection process. Data were analyzed using Microsoft Excel. Results: A descriptive analysis involving 345 paediatric patients presented the prevalence and pattern of LA across different age groups. The mean age of participants was 29 months (±7 months). The majority of patients were in the toddler group (39.13%), followed by infants (32.75%) and older children (28.12%). The most frequent cases were observed in urban areas (54.2%). The most prevalent type of LA was complete adhesion, which represented 97.67% of cases, particularly among toddlers (41.67%). Furthermore, recurrence of LA was observed in 10.14% of patients, predominantly in older children. Conclusion: This study highlighted the distribution and patterns of labial adhesion, revealing a higher prevalence among toddlers and in urban areas. Complete labial adhesion was identified as the most common type. Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):45-51